Ocular surface disease: a known yet overlooked side effect of topical glaucoma therapy - Ruiz-Lozano, Raul E.; Azar, Nadim S.; Mousa, Hazem M.; Quiroga-Garza, Manuel E.; Komai, Seitaro; Wheelock-Gutierrez, Lorena; Cartes, Cristian; Perez, Victor L. (Frontiers in Toxicology, 2023)
Ocular surface disease (OSD), a disorder affecting the lacrimal and meibomian glands and the corneal and conjunctival epithelium, is a well-known complication of topical glaucoma therapy. OSD can present as a new or pre-existing condition that virtually any anti-glaucoma formulation can exacerbate. As such, both glaucoma and OSD frequently coexist. Typical OSD symptoms include ocular discomfort, redness, burning, and dryness, whereas signs include periorbital and eyelid skin pigmentation, conjunctival scarring, and superficial punctate keratitis. Pressure-lowering eyedrops can cause toxic, allergic, and inflammatory reactions on the ocular surface. The latter can result from either preservatives or direct toxicity from the active molecule. Although usually mild, OSD can cause significant symptoms that lead to poor quality of life, decreased compliance to therapy, glaucoma progression, and worse visual outcomes. Given the chronic nature of glaucoma, lack of curative therapy, and subsequent lifelong treatment, addressing OSD is necessary. This manuscript aims to provide an up-to-date overview of OSD’s signs, symptoms, and pathogenic mechanisms from glaucoma therapy toxicity.